2019
DOI: 10.3390/app9142877
|View full text |Cite
|
Sign up to set email alerts
|

Area-Efficient FFT Kernel with Improved Use of GI for Multistandard MIMO-OFDM Applications

Abstract: This study presents a fast Fourier transform (FFT) kernel for multistandard applications, which employ multiple-input, multiple-output orthogonal frequency-division multiplexing (MIMO-OFDM). The proposed design uses a mixed-radix, mixed-multipath delay-feedback (MRM2DF) structure, which enables 4/5/6-stream 64/128-point FFT. This approach allows the effective usage of guard intervals (GI) in conjunction with a novel resource-sharing scheme to improve area efficiency. An area-reduced constant multiplication uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…B_LSD_RS algorithm scans the integer sequence from low bit to high bit. [37][38][39][40][41][42] Starting with the 0th bit, compare the 0th bits of all elements in the integer sequence number, move the element with the value 0 forward, and move the element with the value 1 back. Because the most bit number TA B L E 1 Sequential B_LSD_RS of eight elements of elements in the integer sequence is m, the algorithm needs to loop m times.…”
Section: Principle Of Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…B_LSD_RS algorithm scans the integer sequence from low bit to high bit. [37][38][39][40][41][42] Starting with the 0th bit, compare the 0th bits of all elements in the integer sequence number, move the element with the value 0 forward, and move the element with the value 1 back. Because the most bit number TA B L E 1 Sequential B_LSD_RS of eight elements of elements in the integer sequence is m, the algorithm needs to loop m times.…”
Section: Principle Of Algorithmmentioning
confidence: 99%
“…B_LSD_RS algorithm scans the integer sequence from low bit to high bit 37‐42 . Starting with the 0th bit, compare the 0th bits of all elements in the integer sequence number , move the element with the value 0 forward, and move the element with the value 1 back.…”
Section: Computational Characteristics Analysis Of Radix Sorting Algomentioning
confidence: 99%
“…The mechanism and implications of boundary effects can be drawn from these parametric studies. S. N. Tang et al [7] reported on "Area-efficient FFT Kernel with Improved Use of GI for Multistandard MIMO-OFDM Applications". This study presents a fast Fourier transform (FFT) kernel for multistandard applications, which employ multiple-input, multiple-output orthogonal frequency-division multiplexing (MIMO-OFDM).…”
Section: Topics Of Selected Papersmentioning
confidence: 99%
“…The zero-padded FFT offers increased frequency resolution by extending the length of the input data sequence in the time domain by padding with zeros at the tail of the discrete-time signal. Because of this, it has been widely used for wireless communications and radar systems that require high-frequency resolution [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%